2006
DOI: 10.1007/s11547-006-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial stenosis: role of virtual endoscopy in diagnosis and follow-up after therapy

Abstract: Our study indicates that virtual bronchoscopy has a high diagnostic potential. The technique, with the integration of MPR images, can be proposed as a preliminary study to obtain accurate characterisation of stenoses, to shorten the time required for the subsequent endoscopic procedure and to plan the most appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
(123 reference statements)
1
10
0
Order By: Relevance
“…Interestingly, investigators used CT and FOB to follow-up patients with endobronchial stents; they, too, concluded that CT can be used for follow-up in this group of patients. In other prospective studies patients with tracheobronchial stenoses were followed-up and found similar result with VB [15,16].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, investigators used CT and FOB to follow-up patients with endobronchial stents; they, too, concluded that CT can be used for follow-up in this group of patients. In other prospective studies patients with tracheobronchial stenoses were followed-up and found similar result with VB [15,16].…”
Section: Discussionsupporting
confidence: 68%
“…The disadvantages of VB include the inability to directly visualize the mucous membranes and perform biopsies [12][13][14]. Only two studies compared the results of FOB and VB in the field of following main airway stenoses [15,16]. This study assesses whether VB can be used for the followup of patients treated for large airway stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover we believe among others that VE may play the role of preliminary study in patients that are not capable to undergo conventional bronchoscopy. In this case the preliminary VE can help to obtain accurate topography of the lesion making the bronchoscopy quicker [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two and three-dimensional (2D, 3D) images generated by CT data, provide additional information regarding airway pathology. A variety of computer processing algorithms can be applied in CT acquired data such as: multiplanar reformatting (MPR), shaded surface display (SSD), maximum or minimum intensity projection (MIP), volume rendering techniques (VRT) and more recently virtual endoscopy (VE) [5-12]. …”
Section: Introductionmentioning
confidence: 99%
“…Focal stenosis is most commonly caused by prior intubation or may be seen in the setting of trauma. Taha and colleagues reported superior intraoperative correlation with CT findings compared with fiberoptic bronchoscopy in a small series of patients, further underscoring that CT is a valuable alternative to bronchoscopy in specific cases and can be a useful adjunct for follow-up (19)(20)(21)(22). Postintubation stenosis in particular represents the most common indication for tracheal surgery (19).…”
Section: Laryngotracheal Stenosismentioning
confidence: 99%